2010
DOI: 10.1128/mcb.00716-10
|View full text |Cite
|
Sign up to set email alerts
|

CPEB4 Is a Cell Survival Protein Retained in the Nucleus upon Ischemia or Endoplasmic Reticulum Calcium Depletion

Abstract: The RNA binding protein CPEB (cytoplasmic polyadenylation element binding) regulates cytoplasmic polyadenylation and translation in germ cells and the brain. In neurons, CPEB is detected at postsynaptic sites, as well as in the cell body. The related CPEB3 protein also regulates translation in neurons, albeit probably not through polyadenylation; it, as well as CPEB4, is present in dendrites and the cell body. Here, we show that treatment of neurons with ionotropic glutamate receptor agonists causes CPEB4 to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 54 publications
(54 reference statements)
2
46
1
Order By: Relevance
“…Proteins such as Staufen1 and Staufen2, Translin and Trax, Nova, the ELAV families of proteins as well as numerous other RBPs have been linked to local translation or trafficking, directly or indirectly, in neurons as well as other cell types [77][78][79][80][81][82]. Three other paralogous CPEB proteins (CPEB2, CPEB3, and CPEB4) are also conserved, and expressed in the nervous system [83][84][85]. The available evidence suggests that these proteins are probably not functionally equivalent to CPEB1 despite their similarity and they may mediate translational repression by a different mechanism [86].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins such as Staufen1 and Staufen2, Translin and Trax, Nova, the ELAV families of proteins as well as numerous other RBPs have been linked to local translation or trafficking, directly or indirectly, in neurons as well as other cell types [77][78][79][80][81][82]. Three other paralogous CPEB proteins (CPEB2, CPEB3, and CPEB4) are also conserved, and expressed in the nervous system [83][84][85]. The available evidence suggests that these proteins are probably not functionally equivalent to CPEB1 despite their similarity and they may mediate translational repression by a different mechanism [86].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, potential nuclear localization and nuclear export signals are present within the same domain as well (Ernoult-Lange et al 2009;Lin et al 2010). Although much less is known about the other members of the family (CPEB2-4), their N-terminal domains also appear to contain nuclear import and export signals (Kan et al 2010) and regulatory phosphorylation sites (Igea and Mendez 2010).…”
mentioning
confidence: 99%
“…The research has shown that CPEB4 nuclear accumulation provides protection which is due to the depletion of the ER Ca 2+ store rather than the increase of Ca 2+ in cytoplasm. In addition, IP 3 R, rather than RyR, is responsible for the CPEB4 nuclear import [51]. This elegant experiment highlights that although ER stress induces Ca 2+ loss, the redistribution of CPEB4 between organelles reduces ischemic damage (Figure 2).…”
Section: Ip3rsmentioning
confidence: 94%
“…CPEB4 (cytoplasmic polyadenylation element binding 4) is a typical example. The CPEB family mainly participates in the events of cytoplasmic polyadenylation, translation and RNA transport, but most important are their nucleus-cytoplasm shuttling characteristics [50,51]. In normal conditions, the CPEB4 is located in dendrites and the cell body; while in the rat cerebral ischemia model CPEB4 was found abundantly in the nucleus of penumbra, further suggesting the shuttling feature of CPEB4.…”
Section: Ip3rsmentioning
confidence: 96%
See 1 more Smart Citation